How Much and What Kind of Teaching Is There in Elementary Education in India? Evidence from Three States - Sankar, Deepa (World Bank, Washington, DC, 2014)
This study focuses on the link between teachers' 'time-on-task' (TOT) and the nature of tasks in classrooms. This study, carried out with concurrence from Ministry of Human Resource Development (MHRD), is built upon the independent study commissioned by MHRD to explore teacher attendance rates in schools. This study ventures beyond the quantitative dimensions of teacher attendance (physical presence) to look at the 'time-on-task' (TOT) and nature of tasks, that is, the quantity and quality of teacher presence and interaction. Most specifically, it will provide insight into the work environment of teachers who are the key to service delivery and suggest implications for both policy and program interventions to empower teachers and introduce more accountability into the system. The McKinsey and Company study (Barber & Mourshed, 2007) identified three things that matter most: (1) getting the right people to become teachers; (2) developing them into effective instructors; and (3) ensuring that the system is able to deliver the best possible instruction for every child. In the present study, the attempt is to see whether the teachers are 'effective instructors' and the system is delivering the best to its children. The study aims to find out the factors that facilitate improved quality of instructional time on the one hand, and what it means to the whole process of improving learning levels on the other. In addition, there is an effort to understand the characteristics of various enabling inputs